Customizing surface grafting and interlayer functionalization for PFOA separation in polyamide membranes - Mohsen Pilevar; Hesam Jafarian; Nima Behzadnia; Qiaoli Liang; Sanam Etemadi Maleki; Sadegh Aghapour Aktij; Mohtada Sadrzadeh; Leigh Terry; Mark Elliott; Mostafa Dadashi Firouzjaei (Water Research X)
Emerging contaminants, such as per- and polyfluoroalkyl substances (PFAS), pose significant challenges to ensuring a clean drinking water supply. This study evaluates various fabrication techniques for incorporating silver-based metal-organic frameworks (Ag-MOFs) into polyamide (PA) nanofiltration (NF) membranes to enhance perfluorooctanoic acid (PFOA) separation and anti-fouling performance. Various characterizations, including scanning and transmission electron microscopy, carboxylic group density, molecular weight cut-off (MWCO) measurements, and zeta potential analyses revealed that each method imparts distinct physicochemical and morphological characteristics to the modified membranes. Among all fabricated membranes, the interlayered Ag-MOFs (UI-MOF) obtained the highest permeance (13.7 Lm−2h−1bar−1) but the lowest PFOA rejection (88.9 %), likely due to its loose PA network with large MWCO (522 Da) and high carboxylic group density (82.0 sites/nm2). In contrast, the dip-coating surface-grafted Ag-MOFs (DS-MOF) achieved the highest PFOA rejection (93.4 %), attributed to its narrow pores (average pore diameter of 10 Å ± 0.06). Additionally, all modified membranes showed superior anti-fouling performance (flux recovery ratio > 94.0 %) compared to the Blank PA membrane, likely due to the improved surface hydrophilicity of the modified membranes.